Herbicide use and weed management strategies in hemp cultivation - Navneet Kaur; Anil Kumar; Tabarak Malik; Madhuri Girdhar; Manbir Singh; Reenu Singh; Mohd. Tariq; Anand Mohan (Journal of Cannabis Research)
Abstract Industrial hemp has experienced a resurgence in global cultivation due to its diverse applications in textiles, food, bioplastics, biofuels, and environmental benefits such as phytoremediation and carbon sequestration. However, optimizing hemp production remains challenging, particularly in weed management, where limited approved herbicides and varying regional weed pressures pose significant obstacles. Weed dynamics across different regions highlight the prevalence of problematic species like Chenopodium album and Amaranthus spp. While hemp’s rapid canopy closure and high planting densities can reduce herbicide dependence, early-season weed competition can significantly impact crop establishment and yield. This review explores the current state of weed management in hemp cultivation, highlighting cultural, mechanical, and chemical strategies. Additionally, it evaluates the efficacy and phytotoxicity of pre- and post-emergent herbicides. Recent trials indicate that pre-emergent pendimethalin is consistently safe across multiple studies, while post-emergent grass herbicides like quizalofop, clethodim, and fluazifop provide effective control with minimal crop injury. For broadleaf control, clopyralid and bromoxynil show relative safety, though varietal responses vary. The limited availability of registered herbicides underscores the need for continued research and regulatory advancements. The review identifies critical knowledge gaps, including limited understanding of variety-specific herbicide tolerance and regional weed dynamics. Current research priorities include systematic herbicide screening across varieties and regions, optimizing cultural practices, and developing herbicide-tolerant cultivars. By integrating these strategies, hemp can fulfil its potential as a sustainable and profitable crop, contributing to environmentally friendly agricultural systems. This review provides a foundation for future research and policy decisions to optimize weed management in hemp production.